Migration as a Consequence of Globalization: Migrants’Rights in Globalized World - Gevorgyan, Lilit (Bulletin of Yerevan University C: Jurisprudence, 2024)
Migration has become the most egregious consequence of globalization, as the interconnectedness of economies and societies transcends geographical boundaries across the countries of the world. This paper explores the nexus between migration and globalization, with a specific focus on migrants' rights within the context of a globalized economy. It delves into the challenges and opportunities, positives and negatives presented by globalization for migrants, examining how economic, political, social, cultural, and legal factors influence their rights and experiences. By analyzing existing literature and empirical evidence, this paper seeks to elucidate the complexities of migrant rights in the face of global economic forces. Furthermore, it explores policies and recommendations aimed at promoting the protection and empowerment of migrants in the globalized era. Through this examination, the paper aims to contribute to a deeper understanding of the intersection between migration and globalization and to inform more inclusive and equitable policies for migrants worldwide. By exploring the reasons and interconnectedness of globalization and migration, this paper tries to provide some legal perspectives for future consideration.
Keywords: rights of migrants in a globalized world; causes of migration; globalization and migration; violation of rights of migrants; consequences of globalization